1990
DOI: 10.1161/01.cir.82.4.1325
|View full text |Cite
|
Sign up to set email alerts
|

Onset of altered interventricular septal motion during cardiac surgery. Assessment by continuous intraoperative transesophageal echocardiography.

Abstract: Abnormal motion of the interventricular septum is frequently observed after uncomplicated cardiac surgery. We sought to elucidate the mechanism underlying this phenomenon by using continuous echocardiographic imaging of the heart from a constant transesophageal location in 21 patients undergoing their first cardiac operation. Quantitative global and regional functional analyses were performed in each patient at baseline (stage 1), after median sternotomy (stage 2), after sternal retraction (stage 3), after per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 30 publications
2
25
0
4
Order By: Relevance
“…post-operative septal movement and hypokinesis is commonly observed in patients undergoing open heart surgery, and can affect tissue Doppler imaging of the septum as well [17-19]. A recent study, however, has shown normal septal strain rate after bypass graft surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…post-operative septal movement and hypokinesis is commonly observed in patients undergoing open heart surgery, and can affect tissue Doppler imaging of the septum as well [17-19]. A recent study, however, has shown normal septal strain rate after bypass graft surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of this paradoxical septal movement is not fully understood. Proposed explanations include exaggerated cardiac mobility explained by the lack of restraint of the pericardium (Feneley et al , 1987), events during cardiopulmonary bypass (Lehmann et al , 1990) and systolic translation of the ventricle (Force et al , 1983). In the present study paradoxical movement of the septum could be seen in all patients after coronary bypass surgery and the largest increase in COVV after surgery occurred in a direction similar to this movement (towards the right side of the heart).…”
Section: Discussionmentioning
confidence: 99%
“…This strong interventricular interaction explains the acute changes in LV function seen with abrupt pressure overload of the RV (e.g., from pulmonary embolism), as well as the chronic alterations seen in patients with long‐term RV volume overload (e.g., from pulmonary valve insufficiency) (2). Interventricular septal motion abnormalities are frequently seen in patients after open‐heart surgery (3), but both the cause and effects of this remain unclear (4, 5). In‐depth studies of how the anatomical or functional alternations of one ventricle affect the other have focused on the influence of respiration on cardiac chamber dimensions, and the shape and motion of the interventricular septum.…”
mentioning
confidence: 99%